Cyberchondria and The Psychological Effects of Health Information Online - Sandra, Lidia (Syntax Corporation, 2025)
Many people today experience both higher levels of health anxiety and difficulties with their emotional well-being due to an excessive reliance on the internet to gather health information. This study aims to investigate how excessive health-related internet research impacts anxiety and the need for constant reassurances in adults who use the internet. The goal of this study is to understand how engaging with health information online affects emotions and to determine if digital health literacy plays any role in these relationships. We evaluated associations between cyberchondria, anxiety, and compulsive reassurance-seeking by having 350 participants complete the CSS-15, GAD-7, and a digital health literacy questionnaire. It was found that people with higher levels of cyberchondria often experience more severe health anxiety (β = .56, p < .001) as well as the need for frequent reassurance from others. Those with less digital health literacy experience markedly increased anxiety following their use of internet health resources (p < .01). Having better skills and knowledge to interpret online health information helps to reduce the negative mental health outcomes linked to spending too much time searching for health details online. The results highlight the importance of promoting digital literacy and responsible online health information seeking among the public. Encouraging proper knowledge and counsel for cyberchondria reduces anxiety levels and the burden on healthcare services. This research reveals the influence the internet has over people’s online health-seeking behaviors as well as the associated impact on their psychological well-being.